Computational Thinking of Indonesian Junior High School Students in Solving Geometry Problems - Rianto, Budi; Kusnandi, Kusnandi; Jupri, Al (FKIP Universitas Lampung, 2024)
Mathematics education in the digital era needs to develop computational thinking as a problem-solving skill relevant to the challenges of the 21st century. This skill is closely related to logic and problem solving, which are the core of mathematics learning, such as in geometry. However, how computational thinking is implemented by students when they face geometry problems still needs to be explored further. This study aims to analyze and describe the computational thinking (CT) of junior high school students in Indonesia in solving geometry problems. The Participants were 25 students in grade VIII of an Indonesian junior high school. This study used a qualitative research design. Data collection techniques were carried out through tests and interviews. Data analysis techniques consisted of data reduction, data presentation, and conclusion. The results showed that 60% of students could use CT to solve geometry problems (achieving KKM), while 40% were still below KKM. CT components that students with scores above KKM can achieve include abstraction, decomposition, and algorithms. Meanwhile, students with low scores were identified as having not achieved any of the specified CT components. The computational thinking of junior high school students in geometry has developed quite well. Integrating CT into geometry learning can be a powerful tool for students to solve complex geometry problems. Keywords: computational thinking, problem solving, geometry.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp300-312